Shielded Metal Arc Welding Training Using Virtual Reality - Miranda, Arthur Spinassé; Ferreira, João Vitor Ladislau; Lazarini, Thales Pinheiro; Angeli Neto, Alexandre De; Novais, Matheus Gianordoli; Schimidt, Marcelo Queiroz; Andreão, Rodrigo Varejão; Mestria, Mário (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
The role of welding in various industrial sectors is fundamental and requires both technical skills and well-trained professionals to ensure the structural integrity and safety of welds and welded items. Traditional welding training methods, although effective, tend to be expensive, time-consuming, and expose operators and apprentices to a variety of hazards, such as smoke, heat, and UV radiation. In this sense, Virtual Reality (VR) appears to be a fundamental tool for teaching welding, providing immersive, repeatable, and modular practice environments with efficient use of resources and time. This work presents the development of SMAW welding training software, designed to replicate realistic scenarios in a simulated environment through the use of VR. To quantify the effectiveness and usability of the software, two well-established tools were used: the NASA Task Load Index (NASA-TLX) to measure cognitive workload and the System Usability Scale (SUS) to assess perceived usability. Positive results were obtained, with 47.667 for NASA-TLX and 83.1 for SUS. In addition, the questionnaire about the participants’ experience with virtual reality welding proved to be fundamental to the research, and, like the others, it was administered to 31 students. The tests were carried out with students from technical courses, and the results indicated that the VR software is a viable alternative to conventional training methods. In this sense, the software shows high levels of usability and practicality, which reinforces its potential for application in student training programs.